Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Evaluate the expression, given functions
f
f
f
, and
g
g
g
:
\newline
f
(
x
)
=
3
x
−
2
g
(
x
)
=
5
−
x
2
\begin{array}{l} f(x)=3 x-2 \\ g(x)=5-x^{2} \end{array}
f
(
x
)
=
3
x
−
2
g
(
x
)
=
5
−
x
2
\newline
3
f
(
1
)
−
4
g
(
−
2
)
=
3 f(1)-4 g(-2)=
3
f
(
1
)
−
4
g
(
−
2
)
=
View step-by-step help
Home
Math Problems
Calculus
Find derivatives of sine and cosine functions
Full solution
Q.
Evaluate the expression, given functions
f
f
f
, and
g
g
g
:
\newline
f
(
x
)
=
3
x
−
2
g
(
x
)
=
5
−
x
2
\begin{array}{l} f(x)=3 x-2 \\ g(x)=5-x^{2} \end{array}
f
(
x
)
=
3
x
−
2
g
(
x
)
=
5
−
x
2
\newline
3
f
(
1
)
−
4
g
(
−
2
)
=
3 f(1)-4 g(-2)=
3
f
(
1
)
−
4
g
(
−
2
)
=
Calculate
f
(
1
)
f(1)
f
(
1
)
:
Calculate
f
(
1
)
f(1)
f
(
1
)
using the function
f
(
x
)
=
3
x
−
2
f(x) = 3x - 2
f
(
x
)
=
3
x
−
2
.
\newline
f
(
1
)
=
3
(
1
)
−
2
=
3
−
2
=
1
f(1) = 3(1) - 2 = 3 - 2 = 1
f
(
1
)
=
3
(
1
)
−
2
=
3
−
2
=
1
Calculate
g
(
−
2
)
g(-2)
g
(
−
2
)
:
Calculate
g
(
−
2
)
g(-2)
g
(
−
2
)
using the function
g
(
x
)
=
5
−
x
2
g(x) = 5 - x^2
g
(
x
)
=
5
−
x
2
.
\newline
g
(
−
2
)
=
5
−
(
−
2
)
2
=
5
−
4
=
1
g(-2) = 5 - (-2)^2 = 5 - 4 = 1
g
(
−
2
)
=
5
−
(
−
2
)
2
=
5
−
4
=
1
Multiply
3
3
3
by
f
(
1
)
f(1)
f
(
1
)
:
Multiply
3
3
3
by
f
(
1
)
f(1)
f
(
1
)
.
3
×
f
(
1
)
=
3
×
1
=
3
3 \times f(1) = 3 \times 1 = 3
3
×
f
(
1
)
=
3
×
1
=
3
Multiply
4
4
4
by
g
(
−
2
)
g(-2)
g
(
−
2
)
:
Multiply
4
4
4
by
g
(
−
2
)
g(-2)
g
(
−
2
)
.
\newline
4
×
g
(
−
2
)
=
4
×
1
=
4
4 \times g(-2) = 4 \times 1 = 4
4
×
g
(
−
2
)
=
4
×
1
=
4
Subtract
4
g
(
−
2
)
4g(-2)
4
g
(
−
2
)
from
3
f
(
1
)
3f(1)
3
f
(
1
)
:
Subtract
4
g
(
−
2
)
4g(-2)
4
g
(
−
2
)
from
3
f
(
1
)
3f(1)
3
f
(
1
)
.
\newline
3
f
(
1
)
−
4
g
(
−
2
)
=
3
−
4
=
−
1
3f(1) - 4g(-2) = 3 - 4 = -1
3
f
(
1
)
−
4
g
(
−
2
)
=
3
−
4
=
−
1
More problems from Find derivatives of sine and cosine functions
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
cos
(
x
)
f(x) = \cos(x)
f
(
x
)
=
cos
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
tan
(
x
)
f(x) = \tan(x)
f
(
x
)
=
tan
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
x
f(x) = e^x
f
(
x
)
=
e
x
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
ln
(
x
)
f(x) = \ln(x)
f
(
x
)
=
ln
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
tan
−
1
x
f(x) = \tan^{-1}{x}
f
(
x
)
=
tan
−
1
x
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
x
e
x
f(x) = x e^x
f
(
x
)
=
x
e
x
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
x
x
f(x) = \frac{e^x}{x}
f
(
x
)
=
x
e
x
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
(
x
+
1
)
f(x) = e^{(x + 1)}
f
(
x
)
=
e
(
x
+
1
)
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
x
+
3
f(x) = \sqrt{x+3}
f
(
x
)
=
x
+
3
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
g
(
x
)
g(x)
g
(
x
)
.
\newline
g
(
x
)
=
ln
(
2
x
)
g(x) = \ln(2x)
g
(
x
)
=
ln
(
2
x
)
\newline
g
′
(
x
)
=
g^{\prime}(x) =
g
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant